2012
DOI: 10.1038/bjc.2012.59
|View full text |Cite
|
Sign up to set email alerts
|

Biglycan is a specific marker and an autocrine angiogenic factor of tumour endothelial cells

Abstract: Background:We isolated tumour endothelial cells (TECs), demonstrated their abnormalities, compared gene expression profiles of TECs and normal endothelial cells (NECs) by microarray analysis and identified several genes upregulated in TECs. We focused on the gene encoding biglycan, a small leucine-rich repeat proteoglycan. No report is available on biglycan expression or function in TECs.Methods:The NEC and TEC were isolated. We investigated the biglycan expression and function in TECs. Western blotting analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
127
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 37 publications
6
127
0
Order By: Relevance
“…The proportion of cells in the G0/G1 phase was significantly increased, and the expression levels of the cell cycle-associated proteins, cyclins A and D1, were downregulated, whereas the levels of their inhibitory proteins, p21 and p27, were upregulated. These results were consistent with previously published results, which demonstrated that biglycan may promote cell proliferation and the migratory abilities of cells (25,26). Furthermore, these results indirectly support our previous findings that biglycan overexpression promoted xenograft colon tumor growth, and that the upregulation of biglycan was associated with the malignancy in human colorectal cancer (13,27).…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of cells in the G0/G1 phase was significantly increased, and the expression levels of the cell cycle-associated proteins, cyclins A and D1, were downregulated, whereas the levels of their inhibitory proteins, p21 and p27, were upregulated. These results were consistent with previously published results, which demonstrated that biglycan may promote cell proliferation and the migratory abilities of cells (25,26). Furthermore, these results indirectly support our previous findings that biglycan overexpression promoted xenograft colon tumor growth, and that the upregulation of biglycan was associated with the malignancy in human colorectal cancer (13,27).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in both mouse and human TECs(tumor endothelial cells), BGN was highly expressed, and TEC migration was inhibited after knocking down the BGN. During tumor angiogenesis, the BGN is activated, so it might be a new marker of TECs and may contribute to the anti-angiogenic therapy [27].…”
Section: Discussionmentioning
confidence: 99%
“…BGN, constitutively expressed in normal endothelial cells, becomes significantly overexpressed in tumor tissues and promotes the migration of endothelial cell and neovascularization of cancer [28]. With similar mechanisms, BGN is able to triggering VEGF synthesis in tumor cells, and it has been shown to bind and sequester (VEGFA) in the ECM, thus generating a reservoir of VEGF that can be released during ECM degradation that associated with tumor, capacitating angiogenesis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that biglycan expression is elevated in hepatocellular carcinoma [7], ovarian carcinoma [8], endometrial cancer [9], pancreatic cancer [10], gastric cancer [11], and colon cancer [12] and that biglycan up-regulation is associated with poor prognosis [13,14]. Recent studies have demonstrated that biglycan expression is significantly higher in tumor vascular tissue than in normal vascular tissue; therefore, biglycan can be used as a marker of tumor endothelial cells involved in neovascularization [15]. However, whether it involves in and the underlying mechanism of tumor angiogenesis requires further investigation.…”
Section: Introductionmentioning
confidence: 99%